Introduction of a pictorial poster and a 'crash course' of radiographic errors for improving the qualityof paediatric chest radiographs in an unsupervised unit - Hlabangana, Linda Tebogo (My University, 2014)
Chest radiography is the most commonly performed diagnostic X-ray examination. Optimised image quality is important, particularly in children with radio-sensitive immature organs.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand in fulfillment for the degree of Master of Medicine in the branch of Diagnostic Radiology
Keywords: Radiography, Thoracic--standards